2006
DOI: 10.1016/j.jue.2006.02.005
|View full text |Cite
|
Sign up to set email alerts
|

The impact of local predatory lending laws on the flow of subprime credit

Abstract: Local authorities in North Carolina

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(12 citation statements)
references
References 17 publications
0
12
0
Order By: Relevance
“…In addition, these states tend to have relatively modest restrictions on allowable lending. In particular, four of these five states have 14 Prior research has also found this mixed reaction in the market to the introduction of regulations of high-cost mortgage lending Pennington-Cross, 2006, andLi andErnst, 2006). no provision regarding mandatory arbitration relief.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, these states tend to have relatively modest restrictions on allowable lending. In particular, four of these five states have 14 Prior research has also found this mixed reaction in the market to the introduction of regulations of high-cost mortgage lending Pennington-Cross, 2006, andLi andErnst, 2006). no provision regarding mandatory arbitration relief.…”
Section: Discussionmentioning
confidence: 99%
“…Loan applicants in jurisdictions lacking mortgage information disclosures may perceive greater risks of receiving bad loan offers and decide not to enter the market at all—an example of Akerlof's lemons problem (Akerlof ). Previous studies suggest that state mortgage regulations may encourage more or different types of borrowers to enter the mortgage market, although the effects are neither strong nor consistent (Bocian, Ernst, and Li ; Harvey and Nigro ; Ho and Pennington‐Cross ). There also remains the possibility the laws examined in this study are correlated with other unobserved statewide factors.…”
Section: Discussionmentioning
confidence: 97%
“…With regards to the policy implications, if delinquency results from excessive spending, it would suggest a failure of the pre-contractual regulatory mechanism thereby incentivizing irresponsible lending practices (Ho & Pennington-Cross, 2006;Stoop, 2009;Campbell et al, 2011).…”
Section: Excessive Consumptionmentioning
confidence: 99%